Numerical simulation on sprue distributions during cladding casting process. Issue 8 (7th November 2016) - Han, Xing; Zhang, Haitao; Shao, Bo; Wang, Dongtao; Cheng, Longgang; Guo, Yadong; Qin, Ke; Cui, Jianzhong
Abstract : Purpose: The purpose of this paper is to investigate the influence of sprue distributions on the flow field and temperature field of the cladding casting process and verify the simulation results by experiments. Design/methodology/approach: A steady-state mathematic model for the coupling of fluid flow, heat transfer and solidification to describe the process of cladding casting was present. The effect of sprue distributions on melt flow and temperature field was discussed. Based on the numerical simulation results, the cladding billet was prepared successfully. Moreover, the model has been verified against by temperature measurements during the cladding casting process. Findings: There is a good agreement between the measured and calculated results. The homogeneity of melt flow determines the formability of cladding billets and circular temperature difference affects the bonding of the two alloys. The AA4045/AA3003 cladding billet with no defects in size of f140/f110 mm was fabricated successfully. The alloy elements diffused across the interface and formed diffusion layer with a thickness of 15  µ m. The interface bonding strength is higher than the tensile strength of AA3003, indicating the metallurgical bonding between two alloys. Research limitations/implications: The casting parameters are limited to the aluminum alloy cladding billet in size of f140/f110 mm in this paper. Originality/value: There are few reports of cladding billet, which are used to prepare condense pipes of automotive engines. The effect of distribution schemes on the cladding casting process is rarely studied.